In Vitro Synthesis of Wheat (Triticum aestivum L.) Storage Proteins - Greene, Frank C. (1981)
Free and membrane-associated polysomes were isolated in approximately equal amounts from endosperm of wheat kernels harvested 20 days after anthesis. The presence of heparin in the homogenizing buffer minimized polysome degradation. Ribonucleic acid from the isolated polysomes, when translated in vitro in a wheat germ system, yielded products ranging in size from about 12,000 to about 80,000 daltons, including at least two polypeptides that co-migrated with seed extract proteins in sodium dodecyl sulfate polyacrylamide gel electrophoresis. The nature of the translation products of free and membrane-associated RNA are distinctly different, with membrane-associated RNA yielding a higher proportion of polypeptides in the size range of 30,000 to 37,000 daltons. Analysis of membrane-associated 3′-terminal polyadenylyl-containing RNA in vitro translation products, by solubility in 70% ethanol and by immunoprecipitation, indicates that the 33,000- to 37,000-dalton polypeptides contain gliadins, and the analysis provides evidence that these proteins are synthesized in association with membranous cell organelles. Gliadin polypeptides synthesized in vitro are larger than authentic gliadins and probably are precursors which, in vivo, undergo modification to yield the smaller final products.